2022
DOI: 10.3390/pathogens11060655
|View full text |Cite
|
Sign up to set email alerts
|

Reversion of Ebolavirus Disease from a Single Intramuscular Injection of a Pan-Ebolavirus Immunotherapeutic

Abstract: Intravenous (IV) administration of antiviral monoclonal antibodies (mAbs) can be challenging, particularly during an ongoing epidemic, due to the considerable resources required for performing infusions. An ebolavirus therapeutic administered via intramuscular (IM) injection would reduce the burdens associated with IV infusion and allow rapid treatment of exposed individuals during an outbreak. Here, we demonstrate how MBP134, a cocktail of two pan-ebolavirus mAbs, reverses the course of Sudan ebolavirus disea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The 2013–2016 West African epidemic of EVD that resulted in 28,600 cases and 11,325 deaths demonstrated that filoviruses represent real and great threats to public health. Although progress has been made in developing pan-filovirus mAb-based treatments that can protect NHPs against multiple species of ebolaviruses ( 21 , 22 , 24 ), broad coverage of an anti-filovirus mAb that can also protect against MARV has not yet been formulated.The success of RDV in protecting NHPs against ebolaviruses ( 19 , 33 ) and MARV ( 34 , 35 ) when given after virus exposure shows the promise of small-molecule antivirals that target the filovirus RNA-dependent RNA polymerase. In this work, we show that ODV, an oral prodrug of GS-441524 that is converted into the same active nucleotide triphosphate as RDV, has broad in vitro antiviral activity against EBOV, SUDV, and MARV and can protect NHPs against SUDV when administered 24 hours after virus exposure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 2013–2016 West African epidemic of EVD that resulted in 28,600 cases and 11,325 deaths demonstrated that filoviruses represent real and great threats to public health. Although progress has been made in developing pan-filovirus mAb-based treatments that can protect NHPs against multiple species of ebolaviruses ( 21 , 22 , 24 ), broad coverage of an anti-filovirus mAb that can also protect against MARV has not yet been formulated.The success of RDV in protecting NHPs against ebolaviruses ( 19 , 33 ) and MARV ( 34 , 35 ) when given after virus exposure shows the promise of small-molecule antivirals that target the filovirus RNA-dependent RNA polymerase. In this work, we show that ODV, an oral prodrug of GS-441524 that is converted into the same active nucleotide triphosphate as RDV, has broad in vitro antiviral activity against EBOV, SUDV, and MARV and can protect NHPs against SUDV when administered 24 hours after virus exposure.…”
Section: Discussionmentioning
confidence: 99%
“…For statistical comparisons, survival data from 21 historical positive-control cynomolgus macaques ( 16 , 24 , 31 ) challenged by the same route with the same virus stock and dose were added to the in-study control cohorts. All statistical analyses were performed in GraphPad Prism v10.0.0 and Microsoft Excel.…”
Section: Materials and Methods Summarymentioning
confidence: 99%
See 1 more Smart Citation